The prevalence of and the effect of global stressors on eating disorders among medical students - Almahmeed, Muneera B.; Almutawa, Muna A.; Naguib, Yahya M. (Frontiers in Psychology, 2025)
BackgroundEating disorders (EDs) are among the most serious forms of psychiatric illness, potentially leading to multi-systemic complications. Owing to their high stress levels, medical students are more likely to experience mental health difficulties that predispose them to developing EDs. Societal stigmatization and misinformation, especially in a middle eastern context, contribute to the underreporting and challenges in seeking the appropriate treatment at an early stage, increasing the risk of complications and mortality. EDs remain an under-studied phenomena in the middle east, limiting understanding and treatment options.ObjectiveThe objectives of the current study were to assess the prevalence of EDs, potential contributing factors, and the impact of the COVID-19 pandemic as an independent global stressor among medical students at the Arabian Gulf University.MethodsThis cross-sectional study consisted of a three-part self-administered questionnaire comprising of demographic data, the Eating Attitudes-26 (EAT-26) test, and COVID-19 associated stressors. The study was conducted on medical students at the AGU in the preparatory year up to Year 6. Data was collected from September 2022 to February 2023.ResultsThree hundred and ninety-seven students were recruited in the present study. 32.1% of the tested students demonstrated an elevated risk for developing EDs. Living situation, earlier years of study, and mental health status were significantly associated with increased risk. Response to global stressors such as COVID-19 pandemic was significantly correlated to worsening EDs status in high-risk individuals.ConclusionEating disorders have been discovered to be highly prevalent among medical students, which brings to light an undervalued health concern. This warrants both awareness programs on campus, and the development of individual-tailored eating disorder treatment programs to halt progression and increase overall quality of life and education.